Essential Oils Against Pathogen and Spoilage Microorganisms of Fruit Juices: Use of Versatile Antimicrobial Delivery Systems. Issue 2 (10th January 2017) - Trinetta, Valentina; Morgan, Mark T.; Coupland, John N.; Yucel, Umut
Abstract: Essential oils (EO) are increasingly used as natural antimicrobial compounds, however the effect of delivery system to enhance their antimicrobial activity has not been widely studied. Limonene (0 to 10 μL/mL) was added to microbial suspensions (∼10 5 CFU/mL) of selected foodborne pathogens ( Listeria monocytogenes Scott A, Salmonella enterica Typhimurium, Escherichia coli and Staphylococcus aureus ), and spoilage microorganisms ( Lactobacillus plantarum, Saccharomyces cerevisiae, and Candida albicans ). S. aureus was found to be the most sensitive foodborne pathogen while Salmonella enterica showed continued growth under all concentrations. Stable nanoemulsions and solid lipid nanoparticles (SLN) ( d ∼ 170 nm) were prepared using an alkane carrier oil (n‐tetradecane and n‐eicosane, respectively). Interfacial effects and homogenous distribution of limonene in nanoemulsions improved its (8 and 12 μL/mL) antimicrobial effect against S. aureus . Higher aqueous concentrations as a result of expulsion from SLN further enhanced the antimicrobial activity pronounced at higher limonene concentrations. Therefore, our findings confirm that the emulsion‐based delivery systems are able to effectively distribute limonene inside a microbial suspension to improve its antimicrobial activity.